The Effectiveness of Fun Game Kahoot as A Media in the Teaching of Vocabulary - Antika Mega Mawarni; Suwandi -; Dias Andris Susanto (Institut Agama Islam Negeri (IAIN) Manado, 2021)
This research aims to know the significant difference of using fun game Kahoot to students in learning the vocabulary mastery of Senior High School. The objectives of the study are; (1) to find out the students’ ability in vocabulary who were taught with fun game Kahoot (2) to find out the students’ ability in vocabulary who were taught without fun game Kahoot (3) to find out the significant difference on vocabulary mastery of the eleventh-grade students who were taught using fun game Kahoot and who were taught without using fun game Kahoot. This research was going through quasi-experimental design consisted of two classes. 36 XI MIPA 4 and 35 XI MIPA 3 of SMAN 1 Boja in the academic year 2021/2022 was taken as the sample. The instrument was valid and reliable, the difficulty level was categorized as a medium, and the discriminating power was organized well. It can be known by the result of data. The researchers using SPSS in this research. The data collected were analyzed using a t-test. It was found that the students’ ability to learn vocabulary taught with fun game Kahoot was improved. The student's ability to learn vocabulary that was taught without fun game Kahoot was poor. The value of the t-test was higher than the t-table (20, 04>1, 67). It means teaching vocabulary using the fun game Kahoot was effective. At last, the paper proposed suggestions for teachers to using fun game Kahoot in teaching vocabulary.Keywords: Fun Game Kahoot, vocabulary, effectiveness